2020
DOI: 10.9734/ajmah/2020/v18i130175
|View full text |Cite
|
Sign up to set email alerts
|

Shapes and Sizes of Sella Turcica Using Computerized Tomography (CT) from Tertiary Hospital in Sokoto, Nigeria

Abstract: Cephalometry deals with measurement of body parts or radiological specimen. Sella turcica is an important anatomical structure located in the middle cranial fossa, housing the pituitary gland. Various shapes and sizes of the sellae turcica were reported. In this study, using computerized tomographic (CT) scans from a tertiary hospital, one hundred and seventy five (175) scans were analyzed using Radiant version 4.2 (Medixant 2017) for determination of sizes and shapes of the sella. Average dimensions from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Usman et al [26] found that the normal shape was the most common form of ST in their studied population.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Usman et al [26] found that the normal shape was the most common form of ST in their studied population.…”
Section: Discussionmentioning
confidence: 86%
“…Usman et al [ 26 ] found that the normal shape was the most common form of ST in their studied population. The findings in this study are consistent with other studies where the normal shape was also the most common form of ST, with the oblique shape being the second most common variation morphology of ST [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indian males had larger Sella length, depth, APD compared to female with significant difference for depth only (Gargi et al, 2019). Nigerian males had significantly larger Sella length and APD compared to females (Usman et al, 2020). Sella length was significantly larger in Italian males compared to females (De Donno et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sathyanarayana et al, 1 Al-Mohana et al 4 and Axelsson et al 7 observed a significant difference only in the length of the sella between the genders, whereas Ghaida et al 23 observed only a significant difference in the height of the sella. According to Usman et al, 24 computerized tomography was used to analyze the dimensions of the sella and concluded that males possess significantly larger sellae than females, especially regarding diameters and lengths. From approximately 1 to 13 years of age, Silverman 10 found that males had a larger pituitary fossa than females.…”
Section: Discussionmentioning
confidence: 99%